Influência da aplicação sônica de cimentos resinosos autoadesivos na resistência de união de pinos de fibra de vidro - LINHARES, Thátyla Silva (2016)
Introduction: Although development of self-adhesive dental cements, the cement of the glass fiber post (PFV)is still a challenge. Objective: This study evaluated the influence of sonic insertion adhesive cements in PFV bond strength. Methods: 80 bovine incisors were used randomly divided into eight experimental groups (n = 10), according to the type of self-adhesive resin cement used and insertion technique, conventional (Centrix) and experimental (Application Sonic). After the storage period, the roots were cut yielding six slices, two for each root and the third push-out test was performed. Results: Statistical analysis was performed using the Sigma Plot 12 software and bond strength data were submitted to ANOVA Two-Way. The interaction between the main factors, self-adhesive resin cement and type of participation was significant (p = 0.002). The highest bond strength values were obtained with the U200 cement (26.9 ± 3.5) and Bifix (27.1 ± 4.3) used with ultrasonic application. Conclusion: The insertion of the resin self-adhesive cement with a sonic device to a 170 Hz oscillation frequency promotes increased bond strength to the U200 and Bifix cements.